Bacterial pneumonia in patients with liver cirrhosis, with or without HIV co-infection: a possible definition of antibiotic prophylaxis associated pneumonia (APAP). Issue 2 (1st February 2018) - Cuomo, Gianluca; Brancaccio, Giuseppina; Stornaiuolo, Gianfranca; Manno, Daniela; Gaeta, Giuseppe L.; Mussini, Cristina; Puoti, Massimo; Gaeta, Giovanni B.
Abstract: Introducion: Bacterial infections frequently complicate liver cirrhosis. The aim of this study was to identify risk factors and clinical impact of bacterial pneumonia in patients with cirrhosis. Materials and methods: Bacterial infection prevalence study: consecutive patients with cirrhosis were enroled over a six-month period in 13 Italian centres. Pneumonia and other infections were diagnosed by standard methods. Pneumonia study: cirrhotic patients with pneumonia were enroled for an additional six-month period and HIV-positive patients were included. Results: Pneumonia was the fourth most frequent infection. In the two parts of the study, 79 cases of pneumonia were recorded and 441 patients with cirrhosis without infections served as controls. Seventy-eight patients had extra-pulmonary infections. There were no clinical differences between HIV-negative and -positive cases with pneumonia. Previous gastro-intestinal bleeding ( p  = .02) and long-term prophylactic antibiotic use ( p  < .0001) were associated with pneumonia. Hospital stay was longer and renal failure more frequent than in patients without infections. Pneumonia was hospital acquired (HAP) in 6 cases, healthcare associated (HCAP) in 24 and community acquired (CAP) in 28. A new category of antibiotic prophylaxis associated pneumonia (APAP) was proposed for 21 cases. Cultures were positive in 21/79 patients (26.6%) with Gram-positive isolates in 57%. Unfavourable outcomes were recorded in 11.4% of the cases (3.6% of CAP, 33% of HAP, 12.5% of HCAP and 14.3% of APAP). Conclusions: Receiving antibiotic prophylaxis was associated with pneumonia and the study identified a new sub-group of patients, who require broad spectrum initial antibiotic therapy.